PENGEMBANGAN MEDIA PUZZLE HURUF UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS I PADA PEMBELAJARAN PANCASILA DI SEKOLAH DASAR - Jefry Julianto; Asrial; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is based on the limited use of learning media which causes students' learning outcomes to be classified as low. This research was conducted with the aim of developing a design, measuring feasibility, and assessing the effectiveness of the letter puzzle board media to improve the learning outcomes of grade I students at SD Negeri 56/I Desa Aro. The type of research used is Research and Development (R&D) using the ADDIE development stages. Techniques in data collection through interviews, observations, documentation, written tests and questionnaires. While the data analysis techniques are in the form of normality tests, T tests, and N-gain tests. The research findings show that the letter puzzle board learning media received the